Stanley, Flat Again - Brown, Jeff 1926-; Nash, Scott 1959- (New York : HarperCollins Publishers, 2003)
After Stanley Lambchop goes flat once again, he uses his flatness to help win a sailboat race and to rescue a classmate from a collapsed building.
Keywords: Sailing -- Fiction; Fiction